Hai'ah As-syar'iyyah Al-wathoniyah Wa Dauruha Fi Ar-riqobah Asy-syar'iyyah 'Alal Mashorif Al-Islamiyah Fi Indunisiya Wa Manhajuha Fil Fatwa - Syamsuddin, Hatta, Dr. M. Mu'Inudinillah Basri, MA, Dr. Moh. Abdul Kholiq Hasan, M.A, M. Ed (2016)
The emergence of Islamic banking was considered as a response to the desire of Muslim communities to disassociate from usury (riba based) system, which has rotten in Muslim countries since the period of imperialism. Islamic banking became a very important matter and considered as the modern day requirements of economic and social necessity for Muslim communities because of its sublime goal. The development of time increasing the diversity of financial transactions, both in trading and banking business, which has no provisions in the old sources of Islamic jurisprudence. This dangerous phenomenon was the reason for the importance of a Sharia Supervisory Board to ensure all of banking transactions comply with the rules and principles of sharia. This research focused on sharia supervision on Islamic banking in Indonesia, especially about National Sharia Board. This research applied qualitative analytical descriptive methodology by collecting, reading, and analyzing references about the research topic. The limitations of this research were about: how the sharia supervision system implemented on Islamic banking in Indonesia, how the National Sharia Board played their roles and faces the challenges in performing their activities, and how the method applied by the National Sharia Board in issuing a fatwa. After conducting research and analysis on several references and experiences in the field, the research found that: the National Sharia Board in Indonesia has played their roles, especially in developing Islamic finance industry, ensuring financial and banking transaction comply with the rules and principles of sharia, and providing awareness and guidance to the Muslim communities. There were challenges, internally and externally, facing by the National Sharia Board in Indonesia. Internal problems around on human resources quality, while external problems were about legislation support and various public opinion in society. The issuing of fatwa on financial transactions was the authority of the National Sharia Board. The National Sharia Board hold on procedures, specific steps, and certain agreed methodology in issuing fatwa. Nevertheless, there still some fatwas that caused controversy in the Islamic community.